Effect of crop diversification and sowing technique on productivity, economics, water productivity and soil properties of wheat (Triticum aestivum)-based cropping systems - SINGH, Y P; TOMAR, SANDEEP S; GURJAR, RAVI S; SINGH, SUDHIR (The Indian Journal of Agricultural Sciences, 2024)
Conventionally intensive tillage and sowing practices, and existing cereal crop-based system has been declining soil fertility resulting in poor grain yield and quality. In order to enhance system-based productivity and it becomes necessary to diversify cereal crop through legume-based cropping system with conservation technology-based tillage and crop sowing method. Hence, a study was carried out during 2018–2022 under Farmer First Project (FFP) at Morena district in Madhya Pradesh (Rajmata Vijayaraje Scindia Krishi Vishwa Vidyalaya, Gwalior, Madhya Pradesh) to collate the wheat (Triticum aestivum L.)-based four cropping systems with rainy (kharif) season crops i.e. pearl millet [Pennisetum glaucum (L.) R. Br.], pigeonpea [Cajanus cajan (L.) Millsp.], greengram [Vigna mungo (L.) Hepper] and clusterbean [Cyamopsis tetragonoloba (L.) Taub] and two crop sowing methods, viz. conventionally tilled and permanent broad-bed furrow irrigation were used. Significantly greater improvements were recorded in grain yield of wheat-based cropping systems, net returns, wheat equivalent yield, system protein production, water productivity, net energy gains, energy productivity and soil physico-chemical properties, while saving cultivation cost, total water- use and energy input under permanent broad bed-furrow over conventional tillage and sowing method. Likewise, system-based wheat equivalent yield, system protein productivity, additional net returns, net energy gains, energy productivity and parameters of soil physico-chemical properties were significantly enhanced with pigeonpea-wheat as compared to pearl millet-wheat cropping system. The results of experiment had suggested that cropping system of wheat based can be made more productive and remunerative with the inclusion of legume crops in rainy season and sowing of crop with permanent broad-bed furrow irrigation method.